Unveiling the benefit of germinated colored rice extract to decrease metastatic potential of colorectal cancer cells - Kittirat Saharat; Natthaphorn Paramee; N. Monique Paricharttanakul; Nuchanart Rangkadilok; Daranee Chokchaichamnankit; Chantragan Srisomsap; Kriengsak Lirdprapamongkol; Jisnuson Svasti; Jutamaad Satayavivad (Journal of Functional Foods)
There is increasing evidence of the health effects of germinated colored rice (GCR). Metastasis, namely the spread of cancer cells to distant sites in the body, is a serious problem for cancer therapy. This study aimed to explore the anti-metastatic potential of GCR extract in HT29 colorectal cancer cells through cell migration inhibition, and to identify target proteins by using proteomic approach. GCR extract at 4 mg/mL caused 87 % reduction in cell migration. Two-dimensional gel proteomic analysis revealed β-actin downregulation in GCR-treated cells. GCR also affected gene expression of actin dynamic regulatory proteins including RHOA, RAC1, and CDC42 genes. Gamma-aminobutyric acid (GABA), a bioactive compound present in GCR extract, could decrease cell migration and downregulated β-actin in the cells, but did not alter expression level of RHOA, RAC1, and CDC42 genes. This study reveals a potential of GCR to be developed as a functional food for assisting the cancer treatment.